A new computational procedure for refrigerant condensation inside herringbone-type Brazed Plate Heat Exchangers. (March 2015) - Longo, Giovanni A.; Righetti, Giulia; Zilio, Claudio
Abstract: This paper presents a new computational procedure for refrigerant condensation inside herringbone-type Brazed Plate Heat Exchanger (BPHE). A transition point between gravity controlled and forced convection condensation was found for an equivalent Reynolds number around 1600. At low equivalent Reynolds number (<1600) the heat transfer coefficients are not dependent on mass flux and are well predicted by a simple model based on the Nusselt (1916) equation for vertical surface. For higher equivalent Reynolds number (>1600) the heat transfer coefficients depend on mass flux and condensate drainage is controlled by the combined actions of gravity and vapour shear. A new model was developed for predicting the heat transfer coefficients in the forced convection condensation region. This new model was also applied to super-heated vapour condensation by using the equation of Webb (1998) to account for super-heating effects. The new computational procedure was compared against data from the literature: the mean absolute percentage deviation between experimental and calculated heat transfer coefficients was lower than 16%.